Giant Piezospintronic Effect in a Noncollinear Antiferromagnetic Metal. Issue 26 (25th May 2020) - Guo, Huixin; Feng, Zexin; Yan, Han; Liu, Jiuzhao; Zhang, Jia; Zhou, Xiaorong; Qin, Peixin; Cai, Jialin; Zeng, Zhongming; Zhang, Xin; Wang, Xiaoning; Chen, Hongyu; et al.
Abstract: One of the main bottleneck issues for room‐temperature antiferromagnetic spintronic devices is the small signal read‐out owing to the limited anisotropic magnetoresistance in antiferromagnets. However, this could be overcome by either utilizing the Berry‐curvature‐induced anomalous Hall resistance in noncollinear antiferromagnets or establishing tunnel‐junction devices based on effective manipulation of antiferromagnetic spins. In this work, the giant piezoelectric strain modulation of the spin structure and the anomalous Hall resistance in a noncollinear antiferromagnetic metal— D 019 hexagonal Mn3 Ga—is demonstrated. Furthermore, tunnel‐junction devices are built with a diameter of 200 nm to amplify the maximum tunneling resistance ratio to more than 10% at room‐temperature, which thus implies significant potential of noncollinear antiferromagnets for large signal‐output and high‐density antiferromagnetic spintronic device applications. Abstract : A giant piezospintronic effect is discovered in a hexagonal noncollinear antiferromagnet, Mn3 Ga. Furthermore, it is found that its Fermi surface and density of states are very sensitive to the spin structure perturbation. Consequently, a nanoscale antiferromagnetic tunnel junction built on Mn3 Ga and operated by piezoelectric strain exhibits a more than 10% tunneling resistance modulation at room temperature.